Effect of dihydroartemisinin on UHRF1 gene expression in human prostate cancer PC-3 cells. Issue 4 (April 2017) - Du, Shijuan; Xu, Ge; Zou, Wenqin; Xiang, Tingxiu; Luo, Ziguo
Abstract : As the second most common cancer in men around the world, prostate cancer is increasingly gaining more attention. Dihydroartemisinin (DHA) has been proven to be a promising anticancer agent in vitro as well as in vivo in accumulating data. However, the detailed mechanisms of how DHA action in human prostate cancer PC-3 cells remain elusive. This study aimed to investigate the effects of DHA, a novel anticancer agent, by inhibiting the expression of ubiquitin like containing PHD and ring finger 1 (UHRF1) in PC-3 cells. The apoptosis and cell-cycle distribution were detected by flow cytometry. Quantitative real-time PCR was performed to examine both UHRF1 and DNA methyltransferase 1 (DNMT1) expressions at mRNA levels, whereas the expressions of UHRF1, DNMT1, and p16 INK4A proteins at protein levels were detected by Western blotting. Methylation levels of p16 INK4A CpG islands were determined by bisulfite genomic sequencing. We showed that DHA induced the downregulation of UHRF1 and DNMT1, accompanied by an upregulation of p16 INK4A in PC-3 cells. Decreased p16 INK4A promoter methylation levels in DHA-treated groups were also observed in PC-3 cells. Furthermore, DHA significantly induced apoptosis and G1/S cell-cycle arrest in PC-3 cells. Our results suggested that downregulation of UHRF1/DNMT1 is upstream to many cellular events, including G1 cell arrest, demethylation of p16 INK4A, and apoptosis. Together, our study provides new evidence that DHA may serve as a potential therapeutic agent in the treatment of prostate cancer.